Congenital heart defects and postoperative follow-up of patients with Williams syndrome as a single center experience and review of the cases from Türkiye - Ali Orgun; Kürşad N. Tokel; İlkay Erdoğan; Birgül Varan; Murat Özkan; Sait Aşlamacı (The Turkish Journal of Pediatrics)
Background. Cardiovascular system involvement is quite common and the leading cause of morbidity and mortality in patients with Williams syndrome (WS), most of whom need surgery. The present study aimed to provide a detailed evaluation of the features of surgical procedures and outcomes of patients with WS given as single-center experience, and additionally to make a detailed review from Türkiye.